Perancangan dan Pembuatan Website E-Commerce pada Toko Aksesoris Komputer di Surabaya - Calvine Jardinia Tanuwidjaja; Alexander Setiawan (Jurnal Infra, 2017)
Competition is a common thing that encountered in business world. Inovation, creativity, and good execution are needed in a competition. The company to be studied is a computer accessories store, stationery, and printing located in Surabaya. For now the company already have 2 stores in Surabaya. The high competition and rapid technological advancement at this time become one of the challenges for computer accessories companies to reach customers who are far from their store.Seeing the needs of computer accessories companies, it is necessary to reach customers who are far from the computer accessories shop. By looking and considering at an opportunity of existing technology then e-commerce website can be applied to this company. By creating e-commerce website, the customer can reach it through the google search engine and can directly shop even though the costumer are not in the store location.The final result of this website creation is it can search the list of products quickly, make a simple purchase transactions, know the status of the order. And easily manage the order status.